Osteopaths' perspectives on patient adherence to self-management strategies: A qualitative content analysis. (September 2021) - Tripodi, Nicholas; Krajina, Tommy; Lea, Nicholas; Giudice, Hamish; Eskaf, Steven; Ojea, Michael; D'Souza, Tristan; McLeod, Gopi; Feehan, Jack
Abstract: Introduction: Self-management strategies (SMS) have been found to positively affect healthcare outcomes. However, clinicians often encounter patients with differing levels of adherence to SMS, making it an imperative to recognise and manage the factors underpinning patient adherence to such strategies. To this end, this study explored practitioner-perceived barriers and enablers that affect patient adherence to SMS. Methods: This study explored 14 osteopathic clinicians' perceptions of factors affecting patient adherence to SMS. Semi-structured interviews underwent qualitatively content analysed using a deductive approach, whereby the data were categorised according to a pre-existing framework. Results: Five overarching factors affecting patient adherence to SMS were categorised from the data: healthcare team and system-related; patient-related; social and economic-related; therapy-related; and condition-related. Each category consisted of an enabler and barrier sub-category. Discussion: Patient education and its effect on patient empowerment was reported to be an important driver in SMS adherence, and hence may contribute to an effective healthcare team. Patient lack of time and negative expectations may stem from patient passivity, but also could have been over-represented due to unconscious practitioner bias. Identification of practitioner views on barriers and enablers to SMS adherence may provide insight into how to mitigate factors that can affect patient health outcomes. Conclusion: Clinician perceived barriers and enablers to SMS span across several categories, underpinned by both patient and practitioner behaviour and attitudes. Understanding and addressing the barriers and enablers to SMS can aid adherence within clinical practice, ultimately improving patient outcomes. Highlights: Healthcare team and system-related factors are common practitioner-perceived enablers to patient self-management strategies (SMS). Patient-related and socioeconomic factors are common practitioner-perceived barriers to patient SMS adherence. This may assist clinicians in improving patient adherence and overall outcomes.